Transmembrane Self-Assembled Cyclic Peptide Nanotubes Based on α‐Residues and Cyclic δ‐Amino Acids: A Computational Study - Blanco-González, Alexandre; Calvelo, Martín; Garrido, Pablo F.; Amorín, Manuel; Granja, Juan R.; Piñeiro, Ángel; Garcia-Fandino, Rebeca (Frontiers in Chemistry, 2021)
Self-assembling cyclic peptide nanotubes have been shown to function as synthetic, integral transmembrane channels. The combination of natural and non-natural aminoacids in the sequence of the cyclic peptides enables the control not only of their outer surface but also of the inner cavity behavior and properties, affecting for instance their permeability to different molecules including water and ions. Here, a thorough computational study on a new class of self-assembling peptide motifs, in which δ-aminocycloalkanecarboxylic acids are alternated with natural α-amino acids, is presented. The presence of the synthetic δ-residues creates hydrophobic regions in these α,δ-SCPNs nanotubes, which makes them especially attractive for their potential implementation in the design of new drug or diagnostic agent carrier systems. Using molecular dynamics simulations, the behaviour of water molecules, different ions (Li+, Na+, K+, Cs+ and Ca2+) and their correspondent counter Cl- anions is extensively investigated in the nanoconfined environment. Structure and dynamics are mutually combined in a diving immersion inside these transmembrane channels to discover a fascinating submarine nanoworld where star-shaped water channels guide the passage of cations and anions therethrough.